OP32 Association between optimal guideline-indicated care and survival in patients with acute myocardial infarction and long-term conditions: a population based cohort study. (2nd September 2017) - Ellis, JA; Bebb, O; Dondo, TB; Hall, M; Gale, CP
Abstract : Background: Acute myocardial infarction (AMI) remains the largest cause of hospitalisation and death in Europe. Long term conditions (LTC) are common in people with AMI and patients with LTCs also experience lower survival. The effect of LTCs on treatment receipt has not been investigated. Methods: Myocardial Ischaemia National Audit Project (MINAP) data for 6 93 388 patients with ST-elevation myocardial infarction (STEMI) and non-ST-elevation myocardial infarction (NSTEMI) were used to investigate associations between LTCs (including diabetes, chronic heart failure, chronic renal failure, COPD, peripheral vascular disease, and cerebrovascular disease) and treatment receipt. Poisson and binomial models were fitted to determine the association between LTCs and receipt of care, with treatment receipt as a count and a binary optimal care vs. sub-optimal care variable (receipt of all eligible care components vs. missing one or more) as the outcome and individual as well as cumulative LTCs as exposures. Model adjustments were informed by directed acyclic graphs. Flexible parametric survival models were fitted to investigate the interaction of LTCs and optimal care, and the impact on survival. Results: Receipt of optimal care was 11.3% (n=78, 376), with patients receiving on average 67% of all care opportunities (Mean 0.67, SD 0.23; Median 0.7, IQR 0.5–0.86). In those with a LTC (n=257, 929), 11% (n=28, 357) received optimal care. Patients with ≥one LTC received 2.7% fewer treatments compared with no LTC (IRR 0.97, 95% CI 0.97–0.98); larger differences of 7.3% and 6.1% were evident, respectively, in patients with chronic heart failure (0.93, 0.92–0.93) and chronic renal failure (0.94, 0.93–0.94). The odds of receiving suboptimal care were not significantly different in patients with ≥one LTC than those with no LTC (OR 1.01, 95% CI 0.89, 1.13), however the odds of receiving optimal care was significantly lower in chronic heart failure (0.53, 0.46–0.61) and chronic renal failure (0.52, 0.44–0.62) compared to patients without these conditions. There were 2 04 667 deaths over a mean follow-up time of 2.25 years. The hazard of death in optimally treated patients with ≥one LTC was double that of those without LTCs (HR 2.18, 95% CI 2.09–2.27) and 2.5-fold in sub-optimally treated patients with ≥one LTC compared with no LTCs (2.60, 2.52–2.69). Conclusion: Patients with LTCs received fewer treatments and were less likely to receive optimal care than those without. Treatment receipt was lowest in chronic heart failure and chronic renal failure. The worst survival was observed in patients with ≥one LTC receiving sub-optimal care.